Effect of Linseed Supplementation on Total Longissimus Muscle Lipid Composition and Shelf-Life of Beef From Young Maremmana Bulls - Conte, Giuseppe; Serra, Andrea; Casarosa, Laura; Ciucci, Francesca; Cappucci, Alice; Bulleri, Eleonora; Corrales-Retana, Leonor; Buccioni, Arianna; Mele, Marcello (Frontiers in Veterinary Science, 2019)
Twenty young bulls from the Maremmana breed were randomly allotted to two dietary groups during the finishing period (approx. 90 days): C diet (without lipid supplementation), and L diet (with linseed supplementation, 20% concentrate feed). The aim was to investigate the effect of dietary linseed supplementation on: 1) intramuscular fat composition, and 2) the shelf-life of minced beef. The L diet did not alter the dressing rate and daily weight gain, whereas the C18:3n-3 content in the intramuscular fat significantly increased (from 0.85 to 1.78 g/100 g of total fatty acid, +109%), leading to a reduction in the n-6/n-3 ratio below 4 and to an increase in the overall proportion of long chain n-3 fatty acids in beef lipids. These effects were principally related to a different distribution of fatty acids between the neutral and polar lipids. The results demonstrated that linseed supplementation modified the lipid composition of beef, without negatively impacting overall productivity, in the period from weaning to slaughter. However, the total amount of n-3 fatty acids provided by beef from young bulls fed the L diet was not sufficient to cover a significant aliquot of human requirements of n-3 fatty acids. This was mainly related to the low level of fat in beef. Comparing beef samples from L animals with samples from C animals, the higher level of n-3 polyunsaturated fatty acids led to a significant reduction of shelf-life starting from two days of storage at 4°C, as a consequence of fatty acid and cholesterol oxidation. L group samples showed a higher level of TBARS (+80%) and COPs (+73%), two important parameters to estimate the oxidation level of beef. This suggests that enriching beef with n-3 fatty acids should be coupled with packaging techniques that take into account the higher susceptibility to lipid oxidation. In conclusion, dietary linseed supplementation led to a higher proportion of n-3 fatty acids in beef lipids, however the natural content of antioxidant substances was not able to protect intramuscular fat from oxidation during storage at 4°C.